2015
DOI: 10.1186/s13054-015-0978-6
|View full text |Cite
|
Sign up to set email alerts
|

Smart Care™ versus respiratory physiotherapy–driven manual weaning for critically ill adult patients: a randomized controlled trial

Abstract: IntroductionA recent meta-analysis showed that weaning with SmartCare™ (Dräger, Lübeck, Germany) significantly decreased weaning time in critically ill patients. However, its utility compared with respiratory physiotherapist–protocolized weaning is still a matter of debate. We hypothesized that weaning with SmartCare™ would be as effective as respiratory physiotherapy–driven weaning in critically ill patients.MethodsAdult critically ill patients mechanically ventilated for more than 24 hours in the adult inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 26 publications
0
37
0
1
Order By: Relevance
“…Trials have demonstrated that application of protocols or guidelines for the weaning process may lead to a decrease in weaning time independent of the mode used, even better than automatic systems [ 46 , 47 ]. The ATS/CHEST guidelines suggest to use ventilator liberation protocols to manage adults mechanically ventilated for > 24 h [ 48 ].…”
Section: Main Textmentioning
confidence: 99%
“…Trials have demonstrated that application of protocols or guidelines for the weaning process may lead to a decrease in weaning time independent of the mode used, even better than automatic systems [ 46 , 47 ]. The ATS/CHEST guidelines suggest to use ventilator liberation protocols to manage adults mechanically ventilated for > 24 h [ 48 ].…”
Section: Main Textmentioning
confidence: 99%
“…Recent advances in mechanical ventilation (NAVA, closed loop) were developed to facilitate weaning in acute care and in prolonged weaning [ 79 ]. Some recent meta-analysis [ 80 ] showed that weaning with closed-loop ventilators significantly decreased weaning time in critically ill patients, however, its utility when compared with respiratory physiotherapist protocolized weaning is still a matter of debate [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 Another example are algorithms developed to facilitate and automatize the weaning process in pressure support ventilation based on patient spontaneous activity (respiratory rhythm, tidal volume) and expired CO 2 . 2,3 A third example are algorithms dedicated to control the airway pressure, called adaptive pressure-controlled mode (or dual mode) like AutoFlow ® (Dräger), VC+ (Puritan Bennett), APV (Hamilton Galileo). 4,5 All these algorithms respect a basic rule: the clinician is aware of their existence and can switch them off or on.…”
Section: Introductionmentioning
confidence: 99%